Sars-Cov-2 Humoral Immune Response in Patients with Cardiovascular Risk Factors: The Community Cohort Study; [Respuesta Inmune Humoral por Exposición a Antígenos de Sars-Cov-2 en Adultos Con Riesgo Cardiovascular: The Community Cohort] - Navarrete-Couble, M; Bachelet-Norelli, V; Silva-Ayarza, I (Medwave Estudios Ltda, 2023)
In response to the Vaccine Advisory Committee and the National Immunization Program recommendations, Chile implemented an early vaccination campaign for the population with vaccines from different laboratories. Studying neutralizing antibody levels in different population subgroups contributes to the establishment of correlates of protection against SARS-CoV-2 infection. In 2022 and 2023, we set up a community cohort of 914 adults with cardiovascular risk factors. In this cohort we are measuring the humoral immune response to SARS-CoV-2 antigen exposure, either by vaccination or infection, as well as the incidence of COVID-19 and other adverse events. This cohort, which we call The COmmunity Cohort, is providing us with valuable information on the levels of neutralizing antibodies and the degree of protection against COVID-19 among these individuals. © 2023, Medwave Estudios Ltda. All rights reserved.